The Narrative Sign in “Next to a high-rise palace” by Najman Yassin - Nabo, Salah Jasim (Journal of Tikrit University for Humanities, 2024)
The narrative sign belongs to semiotic studies, which in its various directions tried to deal with the concept of the sign and move away from its editorial dimension at the heart of applied studies, if both Peirce and Swiss had participated in building the theoretical system around the concept of the sign and its relationship to social life. They stop at the currents and schools that dealt with the sign according to different and changing visions.The literary genre, narrative in particular, stands out as meeting Jacobson’s conditions, specifically the poetic function that makes literature what is it. The process of textual division of a story or novel consists of dividing the text into a group of sections, units, structures, and sequences in light of a set of semantic, formal, and pragmatic criteria, the most important of which are; The visual criterion, the synthetic criterion, the spatial criterion, the factorial criterion, and the semantic criterion.As for the story “Next to a Towering Palace” by the Iraqi storyteller Najman Yassin, it ends the short story collection That Strange River. This story is characterized by the atmosphere of childhood, innocence, and the accumulation of fear, as well as the artistic use of the popular heritage of the city of Mosul. The stories of this group are largely intertwined with biographical and narrative, in addition to the dominance of the (folklore) atmosphere of Mosul.